Photoluminescence of Rare-Earth Ions in the Nanocrystalline GaAs/SnO2 Heterostructure and the Photoinduced Electrical Properties Related to the Interface - Machado, Diego H. O. [UNESP]; Scalvi, Luis V. A. [UNESP]; Bueno, Cristina F. [UNESP] (Mdpi Ag, 2017)
Deposition of an SnO2 thin film was carried out by sol-gel-dip-coating and doped with Ce3+ or Eu3+, and a GaAs layer was deposited by resistive evaporation or sputtering. This investigation combines the emission properties of these rare-earth ions with the unique transport properties generated by the heterostructure assembly. Illumination with light with energy above the GaAs bandgap and below the SnO2 bandgap drastically increases the GaAs/SnO2 heterostructure conductance, which becomes practically temperature-independent. This was associated with the presence of interface conduction, possibly a two-dimensional electron gas at the GaAs/SnO2 interface. This feature takes place only for the sample where the GaAs bottom layer is deposited via sputtering. Irradiation with energies above the SnO2 bandgap only excites the top oxide layer. The heterostructure assembly GaAs/SnO2: Eu leads to emission from Eu3+, unlike SnO2 deposition directly on a glass substrate, where the Eu3+ transitions are absent. Eu emission comes along a broad band, located at a higher energy compared to Eu3+ transitions, which are blue-shifted as the thermal annealing temperature increases. Luminescence from Ce3+ ions in the heterostructure can be detected, but the ions overlap with emission from the matrix, and a cleaning procedure helps to identify Ce3+ transitions.
Keywords: heterostructure; europium; cerium; photoluminescence; interface conduction